Development of a WBGT Index Meter Based on M5Stack Core2 - Varela-Aldás, José (2022)
Environmental working conditions are of crucial importance for job performance. Thus, thermal comfort helps the human body to withstand long working hours without stress. There are several indicators of heat stress, but one of the most complete is the WBGT (Wet Bulb Globe Temperature) index, which considers 3 temperatures to determine the heat stress index, the dry bulb temperature, the wet-bulb temperature, and the temperature of radiation. For this reason, this document describes the process of building a low-cost heat stress meter. Two DHT22 sensors and M5Stack Core2 controller are used that includes a screen for the presentation of the information. The user interface includes buttons for changing the view type to show indoor or outdoor results, as well as the battery level. In addition, all this information is sent to the IoT platform of ThingSpeak through internet access using WiFi communication, this information can be displayed graphically from a web browser and from anywhere in the world. The data are compared with a commercial meter to validate this prototype, obtaining an error of less than 5% and no significant differences were found. In this way, it is possible to offer equipment for industrial solutions, but at a fraction of its cost